Relationship Between Subtypes of Early Life Stressors And Severity of Unipolar Depression - Chowdhury, Debolina ,; Patil, Pradeep Shriram; Behere, Prakash Balkrishna (International Journal of Psychosocial Rehabilitation, 2020)
Depression is a severely disabling condition which may affect a person’s sense of selfworth and eventually can lead to dysfunctional interpersonal relationships, social life, and career. According to the Global Burden of Diseases, Depression is one of the top 3 causes in the world overall, and is predicted to become 2nd in the coming years. The objectives of this study are to find correlation of early life stressors which causes depression later in life and present life stressors which are the precipitating factors for depressive episodes. This will be a cross-sectional study. All due consent will be taken and The Adverse Childhood Experiences Scale, Hamilton Depression rating Scale and Presumptive Stressful Life Events Scale will be applied after confirming diagnosis of depression according to the DSM 5 criteria. According to similar studies conducted previous, we expect to find maximum significant correlation between emotional abuse and depression. Depression is also one of the leading causes of suicide. As per data from World Health Organization, suicide is one of the top ten causes for deaths world wide.(1) As depression is clearly an issue which needs to be addressed currently, it is necessary to be able to intercept the disease at primodial level for which it is necessary to be able to indicate the precursors of the disease. Therefore this may prove to be useful as tools for early screening of depression.